A Discourse Semantic Analysis of the Expository Paragraphs Written by the Eleventh Grade Students of SMAN 1 Kubu in the Academic Year 2013/2014 Based on Systemic Functional Linguistic Theory - ., NI MADE WAHYU SUPRABA WATHI; ., Prof. Dr.I Ketut Seken,MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2014)
This study aimed at describing and explaining the experiential meaning, interpersonal meaning and textual meaning as well as the nature of schematic structure in the students? writings under study. This study used descriptive qualitative approach with content analysis as its technique. In collecting the data, some techniques were used such as content analysis, document analysis and also interviewing. This study involved 24 students of the eleventh grade of SMAN 1 Kubu in the academic year 2013/2014. Thus, the object of this study was 24 students? expository writings analyzed through Systemic Functional Linguistics. From the result of the study, it was found out that the students expressed the experiential meaning by using six process types. Mostly, they used material process in their writings. The students expressed the interpersonal meaning of the text through the use of declarative, imperative, modality and personal pronoun. It was revealed that the expository texts under study were mostly constructed in declarative forms. The students expressed the textual meaning of their expository texts through developing themes and rhemes of the clauses constructing the texts. For that reason, the thematic development or progression was analyzed to recognize the textual meanings. Meanwhile, it was identified that twenty three expository writings were built in three main stages, while there is one text which was constructed in two stages or generic structures. The three stages cover introduction (thesis), main body (arguments) and conclusion (reiteration).keyword : Discourse Semantics, Expository Writing, Systemic Functional Linguistics.